Challenges in construction readiness for BIM-based building projects - Radzi, Afiqah R.; Nur Farhana, Azmi; Syahrul Nizam, Kamaruzzaman; Algahtany, Mohammed; Abdul Rahimi, Abdul Rahman (Taylor and Francis Ltd., 2024)
This study aims to investigate challenges in achieving adequate construction readiness for building information modeling (BIM) based building projects, using Malaysia as a case study. To achieve this aim, 20 semi-structured interviews with BIM professionals were conducted using the purposive sampling method. Then, the data were analyzed using thematic analysis. The study results revealed that the challenges can be categorized into two themes: BIM-related challenges and project-related challenges. BIM-related challenges include knowledge, infrastructure, modeling, adoption, and awareness issues. Project-related challenges include funding, communication, team management, cooperation, timeline, coordination, and change order issues. These findings imply that although BIM offers numerous advantages, its implementation introduces specific challenges that differ from those faced in traditional construction projects. These challenges often revolve around technological adoption, data management, changes in project workflows, and team dynamics. Therefore, investigating the specific challenges in BIM-based construction projects is crucial for achieving project success. This study adds to the existing knowledge by providing valuable insights into the challenges faced during the pre-construction phase of BIM-based building projects. The insights can be used to develop strategies for ensuring BIM-based construction projects are ready for the construction phase.